Impacts of the Weighted Deduction Policy for R&D Expenses on Innovation Additionality of Firms: Empirical Evidence from China - Junling Xu; Tong Wang (Discrete Dynamics in Nature and Society)
Based on the data of 3894 companies disclosed in the 2014–2017 Small and Medium Enterprises (SME) Board and Growth Enterprise Market (GEM) Annual Reports, our research evaluates the impacts of the weighted deduction policy for research and development (R&D) expenses on innovation additionality in the “Propensity Score Matching” (PSM) approach, from the moderation perspective of marketization, market competition, and political connections. The empirical findings are as follows: (1) The weighted deduction policy for R&D expenses has a positive effect on the additionality of input and output. The policy has an “additionality effect” on invention patents and utility patents, but it is not significant on appearance patents. (2) Low degree of marketization and high degree of market competition have positive moderating effects on the additionality of input and output. (3) Political connections strengthen the incentive effect of the weighted deduction policy for R&D expenses on the additionality of input and output. From the perspective of additionality, our research results enrich the literature on studies of incentive effects of policy innovation and also provide empirical support for the adjustment of the weighted deduction policy for R&D expenses.